Public awareness on LGBT among the Kuching resident / Mohd Nazreen Abdul Rahman and Muhamad Nor Hakim Jamel - Abdul Rahman, Mohd Nazreen; Jamel, Muhamad Nor Hakim (2015)
Public awareness are important nowadays due to security and sensitivity issues. There is a low interest in studies which link several issues regarding LGBT with public awareness. Given the sensitive issues regarding LGBT, how the public tolerate with them and several other issues, this study investigates the impact of internal and external issues on public awareness on LGBT. The sample size for this studies is 200 will be conducted in Kuching cities area in order to obtain public feedback which then will answer the relationship between internal and external issues towards public awareness on LGBT. This study also wanted to examine the influence of demographic/gender on public awareness. The study used random sampling technique. In order to investigate all of the objectives of this studies, the researcher used descriptive statistics, correlation and t-test. The final chapter includes a discussion of findings, and limitations and recommendations for future research. From the study there is a weak relationship between internal and external issues on public awareness on LGBT which turns out that the public still has a low awareness on LGBT. However, for the demographic/gender, the study find out that women is more aware towards LGBT.